Localized Palmar-Plantar Epidermal Hyperplasia Associated with Use of Sorafenib - Cicek, Demet; Kandi, Basak; Dagli, Ferda A.; Karaogiu, Aziz; Haligur, Beyzan D. (Adis Int Ltd, 2008)
A 45-year-old man receiving oral sorafenib 400 mg twice daily for metastatic renal cell carcinoma developed pain and rash on his hands and feet 3 weeks after commencement of treatment. Dermatological examination revealed hyperkeratotic plaques surrounded by erythema and with a callus-like brownish-yellow appearance centrally, together with bullae with purulent content under the plaques. Histopathological examination revealed intense hyperkeratosis in the upper part of the epidermis and parakeratosis beneath the epidermis. The integrity of the epidermis was therefore compromised and intense neutrophilic infiltration was seen. The patient was diagnosed on clinical and histopathological grounds as having localized palmar-plantar hyperplasia associated with use of sorafenib, representing the second case reported in the literature. The patient's skin lesions improved markedly after the sorafenib dose was decreased to 200 mg twice daily, a regimen that he continues to take. In the authors' opinion, use of the term localized palmar-plantar hyperplasia, as diagnosed in this patient, is more appropriate in this clinical setting than related terms such as palmoplantar erythrodysaesthesia or hand-foot syndrome.
Keywords: Pegylated Liposomal Doxorubicin; Hand-Foot; Erythrodysesthesia; Toxicity; Therapy; Safety